Un metodo, molti metodi per accostare la complessità le sfide della ricerca in bioetica - Galvagni, Lucia (2023)
The method of research in bioethics can be considered paradigmatic in order to reflect on and understand the specificities and limits of the fields of study that are proposed as multi-, inter- and trans-disciplinary. After illustrating the different levels at which bioethics is articulated, the article illustrates some research conducted with people in situations of disability in order to look at this condition through an "ethical" lense.